Proses Kreativitas dalam Penciptaan Tari Srimpi Pudyastuti - Utami, Hadawiyah Endah (Acintya, 2023)
This  research  is  an  experimental  study  of  creative  process  issues  in  the  creation  of  the  Srimpi Pudyastuti dance, the aim of which is to reveal how creative practice ideas of traditional dance are developed by artists with a background in creativity in the cultural and performing arts realms. The method used is a qualitative research method with a choreographic approach. Data collection, observation, literature study  and  interviews.  The  results  of  the  study  show  that  the  Srimpi  Pudyastuti  dance,  in  its  creative process, uses a combination of the concepts of working on the dance movements of the Surakarta Style and Yogyakarta Style which have been stylized into new forms of movement. The creation was inspired by the realities of life that are happening all over the world, namely the Covid-19 pandemic and the stagnation in the development of the group dance genre, especially the srimpi dance. In the creative process, motion exploration is considered to form space and rhythm as well as the findings of the motions that characterize Srimpi Pudyastuti with her vocal movements using a lot of gliding (floating) motions.Keyword: srimpi pudyastuti, creativity, creative process